2009
DOI: 10.1007/s11307-009-0214-3
|View full text |Cite
|
Sign up to set email alerts
|

NEC Density and Liver ROI S/N Ratio for Image Quality Control of Whole-Body FDG-PET Scans: Comparison with Visual Assessment

Abstract: NEC density, representing count statistics per body volume, reflects the visual image quality assessment and may be utilized for quality control of whole-body FDG-PET images together with the liver ROI S/N ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 8 publications
4
28
0
Order By: Relevance
“…This is consistent with the findings of McDermott et al [16]. Mizuta et al [17] concluded that noise equivalent count density NEC density was a better measure, but this was based on 15 scans and it is not clear whether the difference was significant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the findings of McDermott et al [16]. Mizuta et al [17] concluded that noise equivalent count density NEC density was a better measure, but this was based on 15 scans and it is not clear whether the difference was significant.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have suggested that measures based on NEC may coincide better with physicians’ subjective assessment [9, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…These three parameters are used in this guideline, because they are believed to be good indicators of image quality [2]. These reference values, however, may depend on the PET camera model and the subject body size to some extent.…”
Section: Human Image Quality Evaluationmentioning
confidence: 99%
“…These three indicators are known to be excellent indicators of image quality for whole-body FDG-PET/CT images acquired with a single PET camera model [2]. In the present study, in which image data by 10 PET camera models were merged, visual score presented a weak but significant correlation with NEC patient (r = 0.376, p \ 0.001) and with NEC density (r = 0.432, p \ 0.001).…”
Section: Human Image Quality Evaluationmentioning
confidence: 99%
“…To verify that the images obtained were available for response evaluation in terms of image quality, the liver signal-to-noise ratio (liver SNR) was calculated with the following formula [19]:…”
Section: Image Analysismentioning
confidence: 99%